Plant nutrient uptake by the maize crop under different erosion levels and granitic sandy soils of Zimbabwe - Munodawafa, Adelaide (Midlands State University, 2014)
Sheet erosion selectively removes fine soil particles like organic matter and clay, which are critical in soil productivity as they determine the nutrient-supplying capacity as well as the water-holding capacity of the soils. The process is often insidious and may go unnoticed until yields decline drastically. The use of hybrid seed and fertilizers often masks the seriousness of the problem, but it is not known to what extent. This study, therefore sought to assess the uptake of plant nutrients (N, P, K) under five different erosion levels and two fertilizer levels (normal and double). Different erosion levels were achieved by removing different depths of topsoil (scalping). The results showed that nutrient uptake decreased significantly with increase in erosion (N and P at P<0.001; K at P<0.002). The fertilizer use efficiency decreased drastically from uneroded to severely eroded plots. Doubling the fertilizer amount only increased uptake slightly but fertilizer use efficiency remained overall lower than under normal fertilized plots. Soil conservation is the key to sustained soil productivity through maintenance of soil structure and optimal uptake of water and plant nutrients.